O uso das ervas medicinais e a organização feminina na Aldeia de Açaizal do Povo Munduruku do Planalto Santareno - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
This study aims to present the importance of medicinal herbs and the transfer of traditional knowledge through homemade medicine workshops organized by indigenous women in the Açaizal village of the Munduruku do Planalto people. The research was conducted through the researcher's autoethnography, also drawing upon the Munduruku do Planalto Consultation Protocol and Territorial Management Plan as sources. The work addresses the empowerment and female organization of Munduruku indigenous women in Açaizal village, highlighting the valorization of traditional knowledge through homemade remedies, which also serve as a source of income for the village families.
Keywords: Remédios; Caseiros; Organização; Feminina; Conhecimentos; Tradicionais; CNPQ::CIÊNCIAS HUMANAS